PENGARUH HIDROTERAPI KAKI DALAM MENURUNKAN INSOMNIA PADA LANSIA DI KELURAHAN SUKAMAJU KECAMATAN SAIL KOTA PEKANBARU - Sitorus, M.Hidayat; Sulastio, Agus; Mandan, Ali (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Insomnia is a sleep disorder that is most commonly found in the elderly. Elderly people suffered insomnia because the aging physiological factors that reduced secretion of the hormone melatonin. Feet’s hydrotherapy is one of the non-pharmacological ways by soaking feet in warm water with a temperature of 30-39 degrees Celsius who will give the sopartifik effect or want to sleep effects. The purpose of this study are to identify the Effect of Feet’s Hydrotherapy to Reduction of Insomnia Scores at Elderly in Sukamaju Village, Sail Subdistrict,Pekanbaru City. Design of this research is the Pre-Experimental with an approach One Group Pre Test - Post Test Design. Sample selection was done using Total sampling technique. The research sample that is aged 60-90 years old and suffered insomnia as many as 9 respondents. Analysis of statistical data used is the Wilcoxon t-test. Collecting data using questionnaires Insomnia Rating Scale modified by Jakarta Biological Psychiatry Study Group (KSPBJ) according to the Elderly’s conditions in Indonesia. Results of research, measurement results obtained Mean of pretest score of insomnia are 28,78 and measurement results Mean of Post Test score of insomnia are 23,56. Statistical test results using a Wilcoxon T-Test with α = 0,05 are obtained significance values 0,007 or significance <0.05. The conclusion from this research that there is an influence of feet’s hydrotherapy to decrease insomnia scores in elderly. Suggested feet’s hydrotherapy can be used as one way to decrease insomnia in elderly who experience insomnia.Key Words: Hydrotherapy, Elderly, Insomnia